2012
DOI: 10.1523/jneurosci.2398-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Information Representation and Processing for Goal-Directed Behavior in the Dorsolateral and Ventrolateral Prefrontal Cortex and the Dorsal Premotor Cortex

Abstract: Although the lateral prefrontal cortex (lPFC) and dorsal premotor cortex (PMd) are thought to be involved in goal-directed behavior, the specific roles of each area still remain elusive. To characterize and compare neuronal activity in two sectors of the lPFC [dorsal (dlPFC) and ventral (vlPFC)] and the PMd, we designed a behavioral task for monkeys to explore the differences in their participation in four aspects of information processing: encoding of visual signals, behavioral goal retrieval, action specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 75 publications
8
73
0
Order By: Relevance
“…The prefrontal cortex specifies the spatial and object goals of action [Yamagata et al, 2012]. These can include a series of goals as in planning [Mushiake et al, 2006] or performing [Shima et al, 2007] sequences of action.…”
Section: Remapping Factorsmentioning
confidence: 99%
“…The prefrontal cortex specifies the spatial and object goals of action [Yamagata et al, 2012]. These can include a series of goals as in planning [Mushiake et al, 2006] or performing [Shima et al, 2007] sequences of action.…”
Section: Remapping Factorsmentioning
confidence: 99%
“…Moreover, the left dorsal premotor cortex (PMd) and right inferior frontal gyrus are assumed to reflect the retrieval of S-R bindings (Horner & Henson, 2012;Race, Shanker, & Wagner, 2008). Interestingly, the left presupplementary motor area, and the PMd, areas involved in the selection, preparation, and control of movement (Kennerley, Sakai, & Rushworth, 2004;van Gaal, Scholte, Lamme, Fahrenfort, & Ridderinkhof, 2011;Yamagata, Nakayama, Tanji, & Hoshi, 2012), are in fact related to S-R learning (Race et al, 2008) but neither to NP nor have they been found to be modulated by baroreceptor loading or unloading (Kimmerly et al, 2005). Neural correlates responsible for movement control are therefore likely candidates to prevent automatic S-R retrieval from being disrupted by baro-afferent inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…However, the two areas are involved in different ways: the visual-object feature was represented in the vlPFC when the neural representations of the goal developed, whereas the goal representation in the dlPFC developed independently of any encoding of object features. From a perspective of a categorization, Freedman et al (2001) revealed that lateral PFC neurons categorize visual stimuli as “cats” and “dogs,” whereas the observations made by Nakayama et al (2008) and Yamagata et al (2012) suggest that lateral PFC and PMd neurons categorize visual stimuli as associated with right and left behavioral goals.…”
Section: Involvement Of the Prefrontal Cortex In Conditional Visuo-gomentioning
confidence: 99%
“…Based on these observations, the neuronal activity in the vlPFC and dlPFC was examined while monkeys performed the symbolic cue task involving conditional visuo-goal association (Yamagata et al, 2012). …”
Section: Involvement Of the Prefrontal Cortex In Conditional Visuo-gomentioning
confidence: 99%
See 1 more Smart Citation